THE SINKING EARTH. REVENGE OF THE SOILS: HOW DO WE SURVIVE - Chee-Ming Chan (Penerbit UTHM, 2012)
It is simply a book on how we are running out of good grounds to build and accommodate our species, hence forced to develop on less favourable grounds of poor quality soils. With the tendency of these poor quality soils to undergo subsidence, construction of any kind is not possible without first treating the soils. This is what the book is all about: implementing scientifically formulated engineered methods as anti-sinking countermeasures for the soils. But behold, it is NOT another boring engineering book. It is an ordinary book written for ordinary folks, who want to know why the sinking occurs and how we can effectively prevent it, in no other than ordinary language. We can all be enlightened in engineering matters, without the technical jargons, complex theories and above all, tiresome text! The author did undergo academic training in the relevant field of civil and geotechnical engineering, and is in the employment of an academic institution. Teaching and dabbling with research pertaining to soils, the author considers it a natural call of duty to share the knowledge beyond the walls of the University and league of experts.